PENGARUH KUALITAS LAYANAN DAN KEPUASAN SERTA LOYALITAS PADA PASIEN RUMAH SAKIT GIGI DAN MULUT UNIVERSITAS JEMBER - Satar Satar; Diah Yulisetiarini; Handriyono Handriyono (RELASI : JURNAL EKONOMI, 2016)
; "> Competition in the business world today is increasingly tight. All businessinstitution by all means trying to mempertahan.kan market share that has beenachieved. • Under these conditions more difficult • for a company to penetrate themarket for all companies trying to retain customers who have been able dirailmya.One way that can be done by the company is to improve the quality of service,satisfaction and loyalty to the product and services to its customers. With theimprovement of quality of service, which both will be able to improve customersatisfaction. If customers are satisfied with the overall service, it can create loyalbehavior, which is characterized by repeated visits and can recommend the productto others. The purpose of this study are: (1) To test the strong or the weak impact ofservice quality to satisfaction of patients at the Hospital Dental Jember University.(2) To test the strong or the weak impact of service quality on loyalty of patients atthe Hospital of the University Dental Jember (3) To test the strength or weakness ofthe influence of patient satisfaction with hospital patient loyalty Dental JemberUniversity. The data used in this research is data dalmn Respondents DentalHospital of the University of Jember. The samples used were 120 respondents. Thesampling technique is purposive sampling technique tnenggunakan samplingtechnique with a specific purpose in accordance with the criteria set by theresearchers. The research model developed is composed da: ri 5 variables consistingof 3 va1iabel exogenous, 3 variables